Phytochemical Evaluation and Characterization of Methanol Extracts from the Stem-back of Jatropha curcas Plant - Egbunefu, Chukwudi Omeni; Iyama, William Azuka; Lekia, Gbode, Yenor (European Journal of Applied Sciences, 2022)
The phytochemical screening and characterization of the alkaloid and glycosides fractions of methanol extracts of stem-back of Jatropha Curcas plant were carried out. The phytochemical screening showed that the stem-back had 0.62 ± 0.18% flavonoids, 0.52 ± 0.42% tannin, 6.99 ± 0.37% Saponin, 28.78 ± 0.39mg/100g alkaloid and 51.92 ± 0.35mg/100g glycosides. Furthermore, two fractions of these phytochemicals (i.e. the alkaqloid and glycoside) were characterized using standard methods. The alkaloid fraction was found to contain curcin (0.44 ± 0.20mg/100g), tetramethylpyrazine (1.22 ± 0.12mg/100g), atropin (2.10 ± 0.32mg/100g), diphenoxylate (0.81 ± 0.32mg/100g), curcarcycline A (0.49 ± 0.17mg/100g) and curcain (0.80 ± 0.20mg/100g). The glycoside fraction contained linamarin (0.25 ± 0.09mg/100g), lotaustralin (2.14 ± 0.09mg/100g), prunasin (0.40 ± 0.12mg/100g), dhurrin (2.49 ± 0.32mg/100g), amygdelin (15.90 ± 0.55mg/100g), quabain (3.98 ± 0.45mg/100g), digitoxin (13.69 ± 0.40mg/100g), digitalis (4.14 ± 0.25mg/100g) and dioxin (8.89 ± 0.51mg/100g). These active ingredients found in this herbal plant are of great importance in the pharmaceutical industry and can be harnessed to better the lot of humanity more especially in this Covid-19 era when all hands are on deck to find a possible cure for the pandemic that has ravaged the entire world.